MANAGING SELF-DEVELOPMENT (SELF-CREATION) BY THE TEACHER - Żmudzka, Mirosława (The Modern Higher Education Review, 2021)
The aim of the presented article is to draw attention to the considerations related to self-formation, which are more and more vivid in the pedeutological discourse. Constant professional development in the teaching professions determines the effectiveness of teaching as students’ achievements depend mainly on teacher’s skills. Contemporary expectations towards teachers are definitely different than years ago. It results from changing reality, which imposes the necessity to constantly increase one’s own competencies, not only the professional ones, but mainly those related to personal development. Personal growth is a significant aspect of professional development. Managing one’s own development (self-creation) assumes that a man is a self-creator and the space of self-creation is a new method of experiencing the world and one’s place in it. The article analyses the determinants of the self-creation process and its structure as well as the transgressive behaviours involved in the process. The analysis of the teacher’s functioning as a co-creator of himself is embedded in the trend of the concept of humanistic, emancipatory and cognitive psychology.